Linguocultural Features of Russian and Chinese Proverbs with Component ‘Dream’ - Yanqiu Zhang (Научный диалог, 2023)
This study examines Russian and Chinese proverbs with the component ‘dream’ that have not been previously described in a comparative aspect. Linguocultural characteristics of proverbs in both languages are identified, which indicate common or different cultural-national attitudes. The relevance of the research is determined by the development of intercultural relations between Russian and Chinese societies, their interest in studying foreign languages. It is established that the proverbs with the component ‘dream’ recorded in Russian and Chinese lexicographic sources differ in quantitative and substantive terms. It is revealed that authoritative Chinese dictionaries present 10 proverbs with the component ‘dream’, while Russian dictionaries present 43. A common semantic is found among 3 Russian and 3 Chinese proverbs, which interpret dreams as reflections of people’s thoughts and desires. It is shown that the rest of the proverbs verbalize different cultural attitudes. Russian proverbs are characterized by an attitude towards sleep as a physical state that is necessary, beneficial, and pleasant. In addition, dreams are contrasted with reality, in which their fulfillment may or may not be possible. In Chinese proverbs, individuals are recommended to seize the moment and act in a timely manner to achieve their goals, as well as to be cautious with their words.